Making Materials That Hate Water to Love Water: The Transformative Power of Chemistry - Richard N. Zare (Molecular Frontiers Journal, 2017)
A simple nonaqueous reaction scheme for transforming the surface of plastics from hydrophobic to hydrophilic is presented. The chemical modification is achieved by the base-catalyzed trans-esterification of polyethylene terephthalate (PET), which is a commonly used plastic. Its use in blood collection tubes is discussed. The surface modification is permanent, inexpensive, rapid, and does not release contaminants. It also causes no optical or mechanical distortion of the plastic. This work demonstrates the power of chemistry to transform common materials.